1986
DOI: 10.1109/tac.1986.1104391
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling linear multiinput multioutput plants by dynamic output feedback: An algebraic theory

Abstract: This paper presents an algebraic theory for the design of a decoupling Compensator for linear time-invariant multiinput multioutput systems. The design method uses a two-input one-output compensator, which gives a convenient parametrization of all diagonal input-output (I/ 0) maps and all disturbance-to-output (D/O) maps achievable by a stabilizing compensator for a given plant. It is shown that this method has two degrees of freedom: any achievable diagonal 110 map and any achievable D/O map can be realized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 19 publications
0
24
0
3
Order By: Relevance
“…In [10] it is shown that any achievable diagonal I/O map and any achievable disturbance to output map can be realized simultaneously by a choice of an appropriate TPSC.…”
Section: Problem Statementmentioning
confidence: 99%
“…In [10] it is shown that any achievable diagonal I/O map and any achievable disturbance to output map can be realized simultaneously by a choice of an appropriate TPSC.…”
Section: Problem Statementmentioning
confidence: 99%
“…Solving the problem of developing a decoupling design for linear multivariable control systems has been studied in past decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14]21]. Vardulakis [1] presented a sufficient condition for the existence of a decoupling controller: There is no coincidence of plant poles and zeros in the unstable region.…”
Section: A Review Of Prior Workmentioning
confidence: 99%
“…These cited papers, however, adopted a 1DOF (one-degree-of-freedom) controller structure that imposed restrictions on both performance and stability margin when a decoupling constraint was invoked. An efficient way to overcome this restriction is to exploit a 2DOF controller configuration [9][10][11]. In [9], all decoupling input-output maps were parameterized by stabilizing controllers for a 2DOF controller configuration.…”
Section: A Review Of Prior Workmentioning
confidence: 99%
“…Park and Choi [10] recently proposed a set of necessary and sufficient conditions for the existence of decoupling controllers in the generalized plant model. Another efficient approach to overcome 1-DOF restrictions is by exploiting a two-degree-of-freedom controller configuration [11][12][13]. The literature review suggests that attempts to design a decoupling controller using the norm have been done.…”
Section: Introductionmentioning
confidence: 99%